Characterising subtypes of hippocampal sclerosis and reorganization: correlation with pre and postoperative memory deficit. (24th April 2017) - Prada Jardim, Anaclara; Liu, Joan; Baber, Jack; Michalak, Zuzanna; Reeves, Cheryl; Ellis, Matthew; Novy, Jan; de Tisi, Jane; McEvoy, Andrew; Miserocchi, Anna; Targas Yacubian, Elza Marcia; Sisodiya, Sanjay; et al.
Abstract: Neuropathological subtypes of hippocampal sclerosis (HS) in temporal lobe epilepsy (The 2013 International League Against Epilepsy classification) are based on the qualitative assessment of patterns of neuronal loss with NeuN. In practice, some cases appear indeterminate between type 1 (CA1 and CA4 loss) and type 2 HS (CA1 loss) and we predicted that MAP2 would enable a more stringent classification. HS subtypes, as well as the accompanying alteration of axonal networks, regenerative capacity and neurodegeneration have been previously correlated with outcome and memory deficits and may provide prognostic clinical information. We selected 92 cases: 52 type 1 HS, 15 type 2 HS, 18 indeterminate‐HS and 7 no‐HS. Quantitative analysis was carried out on NeuN and MAP2 stained sections and a labeling index (LI) calculated for six hippocampal subfields. We also evaluated hippocampal regenerative activity (MCM2, nestin, olig2, calbindin), degeneration (AT8/phosphorylated tau) and mossy‐fiber pathway re‐organization (ZnT3). Pathology measures were correlated with clinical epilepsy history, memory and naming test scores and postoperative outcomes, at 1 year following surgery. MAP2 LI in indeterminate‐HS was statistically similar to type 2 HS but this clustering was not shown with NeuN. Moderate verbal and visual memory deficits were noted in all HS types, including 54% and 69% of type 2 HS. Memory deficits correlated with several pathology factors including lower NeuN or MAP2 LI in CA4, CA1, dentate gyrus (DG) and subiculum and poor preservation of the mossy fiber pathway. Decline in memory at 1 year associated with AT8 labeling in the subiculum and DG but not HS type. We conclude that MAP2 is a helpful addition in the classification of HS in some cases. Classification of HS subtype, however, did not significantly correlate with outcome or pre‐ or postoperative memory dysfunction, which was associated with multiple pathology factors including hippocampal axonal pathways, regenerative capacity and degenerative changes.